The Distribution of Private Transfers in the United States and France - Rachel Karen (Luxembourg Income Study (LIS), 2023)
Financial transfers between households provide material and/or symbolic assistance while simultaneously strengthening ties between the givers and the recipients. Prior research has documented much heterogeneity in the prevalence of intergenerational financial transfers and how the size and amounts of such transfers differ across race, ethnicity, and family structure. Yet the need or desire for such financial transfers also depends on the larger institutional environment in which households exist. A comparative study of intergenerational transfers between households in different countries with different welfare states therefore reveals the extent to which public provisions affect private financial transfers between households. In this study I examine the distribution of financial transfers between households in the United States and France using Wave X (2015-2017) harmonized Luxembourg Income Study (LIS) data. Results reveal that there is an unequal distribution of private financial transfers between households across the income distribution and by household characteristics in both countries. Results also provide evidence that public transfers do not "crowd out" private transfers between households and in certain instances significantly augment "income-rich" households. These findings offer a comprehensive view of the distributions of private transfers in the United States and in France and provide a more nuanced understanding of income redistribution in countries with significantly different levels of public support.
Keywords: 330